Insecticidal activity and sublethal effects of Beauveria bassiana (Bals.-Criv.) Vuill. isolates and essential oils against Aphis gossypii Glover, 1877 (Hemiptera: Aphididae) - Mahdieh MOUSAVI; Youbert GHOSTA; Nariman MAROOFPOUR (Acta Agriculturae Slovenica)
The cotton aphid, Aphis gossypii Glover, 1877, is a polyphagous species and one of the most important pests of cucumber crops in Iran. In this study, virulence of three Beauveria bassiana (Bals.-Criv.) Vuill isolates, IRAN 108, IRAN 429C and LRC 137, as well as insecticidal activity of two essential oils extracted from Matricaria chamomilla L. and Cuminum cyminum L. were evaluated against adult stage of A. gossypii under laboratory conditions. The data for life table were analyzed using the age-stage, two-sex life table theory. Results showed that all isolates were pathogenic on aphid, but their virulence was varied in different isolates. The lowest calculated LC50 was belonged to IRAN 429C (3.9 × 104conidia ml-1). The lowest LT50 was obtained at concentration of 108 and 107 conidia ml-1 for IRAN 429C (2.9 and 3.55 days, respectively). M. chamomilla essential oil had the lowest LC50 and LT50 values (19 µl l-1 air and 11.4 h), respectively. Longevity and population growth parameters, including the intrinsic rate of increase (rm), gross reproduction rate (GRR), net reproductive rate (R0), generation time (T) and finite rate of population increase (λ), were affected negatively by both agents. According to the results obtained in this study, both entomopathogenic fungi and essential oils could be used as an alternative to chemical insecticides in aphid IPM programs.